2015
DOI: 10.4103/0970-9290.159164
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of eight putative periodontal pathogens in atherosclerotic plaque of coronary artery disease patients and comparing them with noncardiac subjects: A case-control study

Abstract: It is concluded that CAD subjects had higher prevalence of periodontal pathogens in subgingival biofilms as compared to the non cardiac subjects. Further, the number of bacteria was significantly associated between the subgingival and atherosclerotic plaques of the cardiac patients in south Indian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…Mahendra et al found more bacterial presence in subgingival plaque samples compared to atherosclerotic plaques of coronary arteries, but opposite to our results, T. denticola was the most detected pathogen (66.7% positive oral specimens vs. 51% positive artery specimens). The least detected bacteria in their study was A. actinomycetemcomitans that was found only in 2% of subgingival plaque samples [34]. Another group of Indian researchers found similar distribution of periopathogens in the same oral and arterial samples with exception of P. intermedia which showed higher prevalence in coronaries [9].…”
Section: Discussionmentioning
confidence: 84%
“…Mahendra et al found more bacterial presence in subgingival plaque samples compared to atherosclerotic plaques of coronary arteries, but opposite to our results, T. denticola was the most detected pathogen (66.7% positive oral specimens vs. 51% positive artery specimens). The least detected bacteria in their study was A. actinomycetemcomitans that was found only in 2% of subgingival plaque samples [34]. Another group of Indian researchers found similar distribution of periopathogens in the same oral and arterial samples with exception of P. intermedia which showed higher prevalence in coronaries [9].…”
Section: Discussionmentioning
confidence: 84%
“…The subgingival presence of E. corrodens was significant associated with CV disease in a case control study by Mahendra et al (). In addition, the occurrence of E. corroden s in the atherosclerotic plaque has been demonstrated (Mahendra et al, ).…”
Section: Discussionmentioning
confidence: 92%
“…The subgingival presence of E. corrodens was significant associated with CV disease in a case control study by Mahendra et al (). In addition, the occurrence of E. corroden s in the atherosclerotic plaque has been demonstrated (Mahendra et al, ). Other studies also determined E. corrodens in atherosclerotic lesions of patients suffering from chronic periodontitis as well as in atheromatous plaques from patients with CV disease and periodontitis (Kozarov, Sweier, Shelburne, Progulske‐Fox, & Lopatin, ; Reyes, Herrera, Kozarov, Roldan, & Progulske‐Fox, ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…12 At the same time, Mahendra et al proved that patients with cardiovascular diseases (CVD) exhibit higher levels of periodontal pathogens in subgingival biofilms, and that the amount of subgingival bacteria was significantly associated with the amount of bacteria identified in the atherosclerotic plaques. 13 Various pathogens such as Chlamidia pneumoniae, Porphyromonas gingivalis or Helicobacter pylori were identified in human atheromatous plaques, suggesting that infectious agents present in the systemic circulation could penetrate the vascular endothelium and accumulate within the atheromatous plaques, favoring plaque progression. 1,14-21 Table 2 presents the main types of bacteria from oral microbiota, identified by different studies as related to atheromatous plaque formation.…”
Section: Inflammation -A Common Pathway For Periodontal Disease and Amentioning
confidence: 99%